Improving Model Checking with Context Modelling. (24th September 2012) - Dhaussy, Philippe; Boniol, Frédéric; Roger, Jean-Charles; Leroux, Luka
Abstract : This paper deals with the problem of the usage of formal techniques, based on model checking, where models are large and formal verification techniques face the combinatorial explosion issue. The goal of the approach is to express and verify requirements relative to certain context situations. The idea is to unroll the context into several scenarios and successively compose each scenario with the system and verify the resulting composition. We propose to specify the context in which the behavior occurs using a language called CDL ( Context Description Language ), based on activity and message sequence diagrams. The properties to be verified are specified with textual patterns and attached to specific regions in the context. The central idea is to automatically split each identified context into a set of smaller subcontexts and to compose them with the model to be validated. For that, we have implemented a recursive splitting algorithm in our toolset OBP (Observer-based Prover). This paper shows how this combinatorial explosion could be reduced by specifying the environment of the system to be validated.